2012
DOI: 10.1371/journal.pone.0040287
|View full text |Cite
|
Sign up to set email alerts
|

A Synthetic Peptide with the Putative Iron Binding Motif of Amyloid Precursor Protein (APP) Does Not Catalytically Oxidize Iron

Abstract: The β-amyloid precursor protein (APP), which is a key player in Alzheimer's disease, was recently reported to possess an Fe(II) binding site within its E2 domain which exhibits ferroxidase activity [Duce et al. 2010, Cell 142: 857]. The putative ligands of this site were compared to those in the ferroxidase site of ferritin. The activity was indirectly measured using transferrin, which scavenges the Fe(III) product of the reaction. A 22-residue synthetic peptide, named FD1, with the putative ferroxidase site o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
28
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(37 citation statements)
references
References 43 publications
(66 reference statements)
9
28
0
Order By: Relevance
“…In this same study, a REXXE consensus motif found also in ferritin heavy chain (FtH) was described in APP sequence and it was then proposed that APP possessed ferroxidase activity, thus explaining its putative effect on Fpn-mediated iron export in neurons of APP-null mice [20]. However, posterior studies demonstrated that APP does not possess ferroxidase activity [21,22]. Still, it was shown that APP indeed interacted with Fpn, promoting its stabilization at cell surface, thus influencing cellular iron export in the presence of extracellular apo-transferrin [23].…”
Section: Contents Lists Available At Sciencedirectmentioning
confidence: 81%
“…In this same study, a REXXE consensus motif found also in ferritin heavy chain (FtH) was described in APP sequence and it was then proposed that APP possessed ferroxidase activity, thus explaining its putative effect on Fpn-mediated iron export in neurons of APP-null mice [20]. However, posterior studies demonstrated that APP does not possess ferroxidase activity [21,22]. Still, it was shown that APP indeed interacted with Fpn, promoting its stabilization at cell surface, thus influencing cellular iron export in the presence of extracellular apo-transferrin [23].…”
Section: Contents Lists Available At Sciencedirectmentioning
confidence: 81%
“…83,84 Microtubule-associated protein tau (MAPT) deficiency induces intracellular iron accumulation, which causes degeneration of dopaminergic neurons, leading to parkinsonism with dementia in mice. 85 Tau deficiency impairs ferroportin iron export by retaining APP in the endoplasmic reticulum so that it can no longer be trafficked to the neuronal surface, where it can couple its ferroxidase activity to ferroportin.…”
Section: Iron In Neurodegenerative Disordersmentioning
confidence: 99%
“…They described APP as being ferroxidase-active and assigned this activity to a 21 amino acid sequence (named FD1 for ferroxidase domain 1) within the E2 domain of the protein [159]. The proposition that APP is ferroxidase active has been refuted [160-162], however the conclusion drawn by Duce et al. regarding APP's ability to modulate iron efflux from neurons remains sound.…”
Section: Proteins Involved In the Efflux Of Iron From Bmvecmentioning
confidence: 99%